Life Disrupted and Regenerated: Coping With the ‘New Normal’ Creative Arts in the Time of Coronavirus - Connie Lim Keh Nie; Chong-Lee Yow; Chow Ow Wei (International Journal of Business and Society, 2021)
A global pandemic caused by COVID-19 virus since December 2019 has developed into a fearsome situation more than any common global contagion. In combating COVID-19 worldwide, governments instigated a precautionary cordon sanitaire in various degrees. Live music, cinema and film festivals were inevitably cancelled, causing artists to become alienated from their audience. This paper aims to illuminate how practitioners of the creative industry cope with the drastic disruption due to the COVID-19 outbreak as well as the means of regenerating ‘life’, which refers to that of a creative artist in a narrower sense, and to that of the industry in a broader sense. Adopting a combined methodology of autoethnography and virtual ethnography, the authors explore their encounters with the informants and the development of the creative arts scene. The subject of disruption and regeneration in the creative arts industry is approached through feasible methods and tools they could render in this unique lived experience. They hope to construct a view containing some perspectives on the transcendence of creative practitioners from the disruption to the survival of the pandemic’s impact, as well as the regeneration of how creative arts would persevere in the ‘new normal’ of the post-COVID-19 era.